Performance analysis of a Multi-tone direct sequence code division multiple access (MT-DS-CDMA) system over a nakagami-m fading channel - Salma, Umme; Tanni, Tanzina Rahman; Mourin, Nishat Jahan; Islam, Humayra (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2011.